High concentrate diets altered the structure and function of rumen microbiome in goats - Mao, Jinju; Wang, Lizhi; Wang, Zhisheng; Xue, Bai; Peng, Quanhui; Hu, Rui; Xiao, Jianxin (Frontiers in Microbiology, 2024)
This study used metatranscriptomics to investigate the effects of concentrate diet level on rumen microbiome composition and function in goats. A total of 12 healthy 120-day-old Da'er goats were randomly allotted into two treatments: L group (low dietary concentrate level group, concentrate: forage ratio was 25: 75) and H group (high dietary concentrate level group, concentrate: forage ratio was 80: 20). The study included a 10-day pre-feeding period and a 60-day growth experiment. The results showed that compared with the L group, the average daily gain and the slaughter rate in the H group were increased, while the F/G was decreased; the concentration of lactate and ammonia nitrogen, and the proportion of butyrate and valerate in the rumen of the H group were increased, while the proportion of acetate, and the ratio of acetate to propionate were decreased (P < 0.05).Among rumen bacteria, compared with the L group, the H group significantly decreased the relative abundance of Firmicutes and Fibrobacteria at the phylum level, decreased the relative abundance of Bacteroidetes, Fibrobacter and Sarcina and increased the relative abundance of Clostridium at the genus level, and decreased the relative abundance of Fibrobacter succinogenes, Sarcina sp. DSM 11001, Oscillibacter sp. KLE 1728, and Ruminococcus flavefaciens and increased the relative abundance of Clostridium sp. ND2 and Firmicutes bacteria CAG: 103 at the species level (P < 0.05).Among rumen fungi, the relative abundance of Basidiomycota, Neocallimastigomycota, Mortierella, Mortierella elongata, and Gonapodyna prolifera was lower in the H group than that in the L group (P < 0.05). Functional annotation results showed that the abundance of Glycoside hydrolases genes in rumen microbiome was significantly decreased in the H group compared to the L group (P < 0.05).The result of KEGG DEGs enrichment analysis showed that the gene expression of cellulose 1,4-βcellobiosidase, acetyl-CoA hydrolase, lactate dehydrogenase, succinate-semialdehyde dehydrogenase, D-malate dehydrogenase and related genes in methane production pathways of rumen microbiome was decreased in the H group. In summary, feeding high concentrate diets improved the production performance of goats, altered the structure and composition of rumen microbiome and changed the function of rumen microbiome.